Big Five personality traits in inmates and normal adults in Japan. (15th April 2019) - Shimotsukasa, Tadahiro; Oshio, Atsushi; Tani, Masayuki; Yamaki, Mayuko
Abstract: The purpose of this study was to investigate differences in personality traits among violent, theft, and illegal drug use criminals, comparing them with normal adults. Inmates ( N  = 645) and normal adults ( N  = 4546) in Japan responded to a questionnaire, including the Big Five personality traits. Results indicated that violent criminals tended to show lower Agreeableness and higher Extraversion than other criminals. Theft criminals tended to display low Conscientiousness. Illegal drug use criminals showed higher Extraversion and Openness. Inmates tended to show higher Extraversion, Agreeableness, Openness, and Conscientiousness than normal adults. Characteristics of personality traits of criminals were discussed.